The Potential of Land Abandonment in Bogor Regency for Community Forest Enterprises - Hariadi Kartodihardjo; Dodik Ridho Nurrochmat; Ernan Rustiadi; Handian Purwawangsa (Jurnal Manajemen Hutan Tropika, 2021)
The abandoned land and indicated abandoned land are considered critical land or land that is less productive. Those lands covered about 13,000 ha of Bogor Regency area, with the critical land area of around ​​93,467.51 ha (32%). To reduce the area of critical land and increase land productivity in Bogor can be done by optimizing the abandoned land for private forest use. This study aimed to analyze the potential and opportunities for private forest use in abandoned land. The method used was an investigative approach with quantitative and qualitative descriptive analysis. This study showed that in terms of land characteristics and biophysical conditions, the abandoned land could be developed for private forest business, especially to cultivate forest business, such as sengon (Albizia chinensis), kayu afrika (Maesopsis eminii), jabon (Neolamarckia cadamba), mahoni (Swietenia mahagoni), and kayu manis (Cinnamomum verum). The majority of respondents (65%) were willing to do partnerships in private forests. However, several factors are needed to support this business, i.e., regulations in the form of incentives and disincentives from local governments, investors, facilitators, and market access.